Application of the heat pipe to enhance the performance of the vapor compression refrigeration system - Nakkaew, Santiphap; Chitipalungsri, Thunyawat; Ahn, Ho Seon; Jerng, Dong-Wook; Asirvatham, Lazarus Godson; Dalkilic, Ahmet Selim; Mahian, Omid; Wongwises, Somchai (ELSEVIER, 2019)
This paper presents an application of the heat pipe to enhance the performance of the air conditioner. The study is done in two steps. First, the effect of pertinent parameters on the heat transfer rate of the heat pipe set is investigated. Then the heat pipe set is installed in the split-type air conditioner and tested in the actual condition. The heat pipe set consists of a heat pipe, holder, and plate fins. The length of the heat pipe is 300 mm. The working fluid inside the heat pipe is deionized water. Two different geometries of holder which are A-geometry and B-geometry are used in the study. Both holders are made of copper. The numbers of heat pipe in each set are 2, 4 and 6. The experimental results show that the maximum heat transfer rate obtained from the heat pipe set is about 240 W at the air velocity of 5 m/s and the heater surface temperature of 70 degrees C. The heat pipe set with A-geometry consisting of 6 heat pipes is the best configuration. However, this configuration provides the highest air-side pressure drop because of the highest velocity. The best heat pipe set is installed at the outlet of the compressor in the air conditioner with a cooling capacity of 9,000 BTU/hr. The experimental results show that the energy efficiency ratios (EER) of the air conditioners with heat pipe set are slightly higher than those of the conventional air conditioner. The EER of air conditioners with copper holder of heat pipe increases about 3.11%. The results from the present study are important for enhancing the performance of the vapor compression refrigeration system.
Keywords: Air conditioner; Energy efficiency ratio; Heat pipe; Vapor compression refrigeration system; AIR-CONDITIONING SYSTEM; EXCHANGER; ENERGY; RECOVERY; CONFIGURATIONS; SAVINGS; Thermodynamics